RNA Interference of Human α-Synuclein in Mouse - Kim, Young-Cho; Miller, Adam; Lins, Livia C. R. F.; Han, Sang-Woo; Keiser, Megan S.; Boudreau, Ryan L.; Davidson, Beverly L.; Narayanan, Nandakumar S. (Frontiers in Neurology, 2017)
Alpha-synuclein is postulated to play a key role in the pathogenesis of Parkinson’s disease (PD). Aggregates of alpha-synuclein contribute to neurodegeneration and cell death in humans and in mouse models of PD. Here, we use virally-mediated RNA-interference to knock down human alpha-synuclein in mice. We used an siRNA design algorithm to identify 8 siRNA sequences with minimal off-targeting potential. One RNA-interference sequence (miSyn4) showed maximal protein knockdown potential in vitro. We then designed AAV vectors expressing miSyn4 and injected them into the mouse substantia nigra. miSyn4 was robustly expressed and did not detectably change dopamine neurons, glial proliferation or mouse behavior. We then injected AAV2-miSyn4 into Thy1-hSNCA mice over expressing alpha-synuclein and found decreased human alpha synuclein (hSNCA) in both midbrain and cortex. In separate mice, co-injection of AAV2-hSNCA and AAV2-miSyn4 demonstrated decreased hSNCA expression and rescue of hSNCA-mediated behavioral deficits. These data suggest that virally-mediated RNA interference can knockdown hSNCA in vivo, which could be helpful for future therapies targeting human alpha-synuclein.